Analysis of pile capacity by using static formulas and static load test - Hendeyson Anak Francis Doublin (School of Environmental Engineering, University Malaysia Perlis, 2016)
The ultimate end bearings and skin frictions of piles can be estimated by static methods but between one method and another, the result are still questionable. These studies were focus on driven Spun Pile that constructed in Malaysia in cohesive soils. These were to determine the different between several pile design methods by Meyerhof (1976), Janbu (1976), Vesic (1975), a method (1985) and l method (1972) with the End-bearing capacity and Skin Resistance capacity respectively value with static load test using Maintain Load Test (MLT). The results of the methods were compared with static load test values that interpreted from Chin's Method to determine the most accurate results among the methods. All the design method were analyzed by using the importance parameter such as soil friction angle, undrained shear strength and unit weight of soils. The values of soil friction angle then were used to design a corrected N-value equation. From the analysis it can be found that the Vesic's method was the most value that near to Maintain Load Test value. The value for Vesic's Method were 111KN for borehole 1 and 125KN for borehole 2 and the value for Chin's Method were 122KN. From this study it can be concluded that it is recommended to use Vesic's method for estimating end bearing capacity in cohesive soils. Next, skin friction in cohesive soils it recommend using the Lamda method because the result of Lamda method was the most near to the Chin' Method result. The Value for Lamda method were 1198 KN and meanwhile for Chin;s Method were 2291KN.